Novel nano-submicron mineral-based soil conditioner for sustainable agricultural development. (15th April 2017) - Liu, Shanke; Qi, Xin; Han, Cheng; Liu, Jianming; Sheng, Xuebin; Li, He; Luo, Anming; Li, Jianglin
Abstract: Soil is formed through the weathering of natural rocks, and the solid composition of soil is at least 90% minerals. Soil experiences acidification and heavy metal contamination, and these phenomena are global problems that must be addressed on the basis of green chemistry principles to achieve sustainable agricultural development and maintain a healthy ecological environment. Soil may be effectively remediated by applying mineral-based soil conditioners. In this study, soil formation was simulated and a novel nano-submicron mineral-based soil conditioner was prepared from a potassium-rich feldspar by using an environmentally friendly hydrothermal method to buffer severe acidification and inhibit the phytoavailability of hazardous elements in soil. Field and in-house experiments confirmed that the performance of the proposed soil conditioner as soil amendment was effective. Soil pH was improved by 1%–9% compared with that of the control group, and soil bulk density decreased by approximately 8%. Al concentration in soil decreased by 29%–42% compared with that of the control group, and this observation indicated that aluminum toxicity was alleviated. Cd concentration in the corn of the rice also decreased by 50% compared with the control level, and this result suggested that cadmium accumulation was inhibited. This excellent performance was attributed to multifactor synergy and closely related to the morphology, chemical composition, mineral components, and preparation method of the proposed soil conditioner. Graphical abstract: Highlights: A novel nano–submicron mineral-based soil conditioner (NSMC) was prepared from potassium-rich feldspar. NMSC preparation through rock weathering simulation is a novel concept. NSMC possesses dual functions of nourishing soil and remediating soil. NSMC exhibits good performances in soil amendment. NSMC's excellent performance is a result of multifactor synergy.